The supremacy of God in preaching - Piper, John, 1946- (2021)
"This newly revised and expanded edition of this classic preaching resource is the essential guide for preachers who want to stir the embers of revival. John Piper has added valuable new material reflecting on his thirty-three years of preaching at Bethlehem Baptist Church, offering a glimpse of what a lifetime of putting God first has done for the faith of the hundreds of thousands who have heard him preach over the years"--
Includes bibliographical references (pages 157-163) and indexes.
Keywords: Edwards, Jonathan, -- 1703-1758.; Preaching; Clergy -- Religious life